1991
DOI: 10.1073/pnas.88.4.1207
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and adaptedness in tetraploid Avena barbata and its diploid ancestors Avena hirtula and Avena wiestii.

Abstract: Avena barbata, a tetraploid grass, is much more widely adapted and successful in forming dense stands than its diploid ancestors. The success of such polyploids has often been attributed to heterosis associated with ability to breed true for a highly heterozygous state in which allelic differences between the parents are fixed in the polyploid by chromosome doubling. We have examined the relationship between genetic diversity and adaptedness for 14 allozyme loci inA. barbata and its diploid ancestors in sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…It was argued that the main force responsible for the evolutionary change in the colonial populations of A. barbata was selection for particular combinations of alleles in response to different environments in California (Pérez de la Vega et al . 1991; Garcia et al . 1991; Allard et al .…”
Section: Discussionmentioning
confidence: 99%
“…It was argued that the main force responsible for the evolutionary change in the colonial populations of A. barbata was selection for particular combinations of alleles in response to different environments in California (Pérez de la Vega et al . 1991; Garcia et al . 1991; Allard et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that differences in adaptedness between these two genotypes may have been due entirely to the main effects of these five loci but the very large number of different patterns in which the alleles of the 14-locus genotypes occur in the diploid suggest that two-locus, three-locus and higher-order interactions were also involved . In fact discrete loglinear analyses showed that many multilocus interactions are highly significant statistically but others are nonsignificant (Perez de la Garcia et al ., 1991) . Within-population diversity varied from none for Sites I and 2, to small for Site 3 (only two 14-locus genotypes present), to substantial for Sites 4 and 5 (eight different 14-locus genotypes present), to high for the five remaining sites (13 to 36 different 14-locus genotypes present).…”
Section: Avena Hirtula (Ah) and A Barbata (Ab)mentioning
confidence: 99%
“…In recent years it has been found that examination of changes in the frequencies of discretely distinguishable alleles and genotypes of morphological, disease resistance, allozyme, restriction fragment, and microsatellite loci that occurred during the domestication process allow deductions concerning the genetic mechanisms that have led to improved adaptedness (e.g . Clegg & Allard, 1972 ;Allard, 1988Allard, , 1990 ; Perez de la Vega, Garcia et al ., 1991 ;Allard et al ., 1993 ;Saghai Maroof et al, 1994;Cluster & Allard, 1995) . In all cases that have been studied in detail it has been found that population behavior can be explained on the basis of selection acting on the chromosomal segments in which the marker loci reside ; thus marker assisted dissection of the genetic basis of adaptedness is feasible and a substantial literature has built up, too large to review in the time allotted .…”
Section: Introductionmentioning
confidence: 99%
“…The one percent of outcrossing that occurs leads to recombination that produces numerous different interlocus allelic configurations within local populations, whereas the 99% of selfing restricts recombination sufficiently to protect favorable interallelic associations from being broken up by segregation before they can be tested by selection (11,12). The tetraploidy of A. barbata allows the development and fixation of heteroallelic intralocus associations of alleles (13). Thus the mating system of A. barbata, in combination with differing modes of selection associated with local environmental heterogeneity, appears to have led to the development of a pathwork pattern of differing multilocus genetic organizations in Spain.…”
Section: Loci Of Group 2 (Californian Xeric Allelesmentioning
confidence: 99%